Comprehensive Integration of Single-Cell Transcriptional Profiling Reveals the Heterogeneities of Non-cardiomyocytes in Healthy and Ischemic Hearts - Zhuang, Lingfang; Lu, Lin; Zhang, Ruiyan; Chen, Kang; Yan, Xiaoxiang (Frontiers in Cardiovascular Medicine, 2020)
Advances in single-cell RNA sequencing (scRNA-seq) technology have recently shed light on the molecular mechanisms of the spatial and temporal changes of thousands of cells simultaneously under homeostatic and ischemic conditions. The aim of this study is to investigate whether it is possible to integrate multiple similar scRNA-seq datasets for a more comprehensive understanding of diseases. In this study, we integrated three representative scRNA-seq datasets of 27,349 non-cardiomyocytes isolated at 3 days and 7 days after myocardial infarction or sham surgery. In total, seven lineages, including macrophages, fibroblasts, endothelia, and lymphocytes, were identified in this analysis with distinct dynamic and functional properties in healthy and nonhealthy hearts. Myofibroblasts and endothelia were recognized as the central hubs of cellular communication via ligand-receptor interactions. Additionally, we showed that macrophages from different origins exhibited divergent transcriptional signatures, pathways, developmental trajectories, and transcriptional regulons. It was found that myofibroblasts predominantly expand at 7 days after myocardial infarction with pro-reparative characteristics. We identified signature genes of myofibroblasts, such as Postn, Cthrc1, and Ddah1, among which Ddah1 was exclusively expressed on activated fibroblasts and exhibited concordant upregulation in bulk RNA sequencing data and in vivo. Collectively, this compendium of scRNA-seq data provides a valuable entry point for understanding the transcriptional and dynamic changes of non-cardiomyocytes in healthy and nonhealthy hearts by integrating multiple datasets.